A challenge to objective perception in hearing and seeing in counselling psychology. Issue 8 (7th September 2015) - Baron, Philip
Abstract : Purpose: – Mainstream counselling psychology with its Western epistemology implies several assumptions about the therapeutic conversation. One assumption is the ability of the therapist to hear and see accurately during the therapy session. Apart from language difficulties and multi-cultural awareness, training in psychological counselling does not adequately address aspects of hearing and seeing as cognitive processors that are observer dependent and circular in nature. The purpose of this paper is to address this missing link by providing a single document addressing errors in hearing and seeing, which can then be used for training new therapists. Design/methodology/approach: – Using a Western epistemology, an argument based on multidisciplinary research findings is used to challenge the ideas of objective hearing and seeing in the therapeutic conversation of the counselling activity. Findings: – Research findings show that the act of hearing and seeing are personal and subjective. This would be in keeping with a cybernetic epistemology; however, cybernetic psychology is not well known nor widely accepted in mainstream institutions. Teaching counsellors who have a Western epistemology poses challenges when attempting to negate the objective reality of the trainees. Training counsellors to incorporate a cybernetic ethic of participation has obstacles, especially when the training has time constraints. Using Western positivistic research findings as a basis for providing an argument for subjectivity in perception may be a quicker method to achieve at least partial observer dependent thinking for counsellors in a short-time space during training sessions. Research limitations/implications: – This paper presents a concentration of multidisciplinary research that can be used as part of counsellor training for the purposes of providing a basis for the error and filtering that take place in human perception of sound and vision. Originality/value: – The modalities of hearing and seeing are not readily addressed in counselling psychology praxis. The errors in human sense perception are integral in framing the therapeutic conversation as one of subjective co-construction between observers, moving closer to an empathetic position. This paper provides a research-based argument in denying objectivity in human perception during the therapeutic conversation.